PENERAPAN MODEL BLENDED LEARNING PADA PEMBELAJARAN SENI BUDAYA DI SMA DENGAN SISTEM UKBM - Ahdhani Fajar Seffendy (Jurusan Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2021)
In educational technology, information and communication technology are massively used to support various interests. Learning system (UKBM) or Independent Learning Activities Unit in high school can use a blended learning model. This writing uses literature review. Aiming to find out of effectiveness of implementation the cultural arts learning in the system high school through models of blended learning. With the model, UKBM system learning is expected to accommodate the needs of students and can effectively utilize information and communication technology. Based on components in blended learning, the underlying learning theory is constructivism learning theory. Which encourages building knowledge based on individual experience and applying it directly to the environment.